Assessment and Comparison of Cable-Actuation of Pill Bug Inspired Adaptive Origami Structure Using Computer Vision and Dynamic Relaxation - Baruah , Angshuman C.; Sychterz , Ann C. (Frontiers in Built Environment, 2022)
The ancient art of origami can be harnessed for the development of adaptive structures including those at civil-engineering scale. This can be enhanced with biomimetics, the study and development of synthetic mechanisms that mimic the structure or functionality of biological organisms in nature. The origami structure presented in this paper draws inspiration from pill bugs, a species of woodlice that can alter its shape between a flat and a rolled configuration. The panel-type origami pill bug structure is modeled as bars, hinges, and active elements for actuation. This paper provides analysis and comparison of a new formulation of the form-finding method called dynamic relaxation for the analytical study with a computer vision algorithm for the experimental study of a 3D-printed model. The objective of this study is to simulate and experimentally validate the quasi-static and dynamic response to characterize the kinematic properties and dynamic behavior of the origami pill bug structure.